منهج الإمام ابن حزم الظاهري في تأصيل القواعد الفقهية - - سليمان خرصي; أبوبكر الصديق دير; د/ أمحمد علالي (جامعة عمار ثليجي الاغواط, 2023)
الاع ن لله ر الع ملععن وال وال م عل س ن ع الك رعم، و ع ن: م نْ اثن م العو وم : ع ن ج الإمام ابن حزم الظاهري في تأصيل القواعد الفقهية دراسة تطبيقية ، ع كر عنع لنع ش من العم رَ م ال الع مرن و ول ،َ - - اش عَلا عل س عنع وم لعن وخم عَ ، و نمنم ع ن خ النرا عمط اللث مم ع ن الشخ ع العلعع ل ع مم ا ن ا مَ، مء ال الأو م ع اث عن، و عن الع ا الأو رَ ع ع و ل ع مم ا ن ا مَ، واا وى الع ا الث من عل س ع نخ ل س عل م الواع ن ال ع ش ء ع ن ال َ ع ، اع كرن م عَرع م لعل م الواع ن و عين م عع وا ع و م ال رول، ث م ك من العع م ال الث من ع ن ع اث عن، اع عن الع ا الأو را م العع ملم والأ و ال اع عَ ن م ا ن ا مَ م أَ عل للواع ن ال ع ، والع عَثل م : ان عَنان، ال عم ، الن ن، انن ران، ث م كرن م م الع ا الث من ع م ال طَ ع ما للواع ن ال ع ، وخ مَع م وَ لنم ل س م الن مئج، و ن الإع مم ا ن ا مَ ع ن ال يمقعن م عل م الواع ن ال ع ، وشعين را و ثرى ع عون ،َ وع ي ن الإعمم منيم ع َ . Summary of the dissertation: Praise be to Allah, Lord of the Worlds, and peace and blessings be upon His Holy Prophet. Our research tagged with: The approach of Imam Ibn Hazm Al-Dhaheri in rooting the rules of jurisprudence - an applied study - is an introduction to obtaining a master's degree in comparative jurisprudence and its origins, which included an introduction, two chapters and a conclusion in which we dealt with: In the first chapter a translation of Imam Ibn Hazm and an introduction to the science of jurisprudence rules in some detail, then the work was in the second chapter of the two sections; the first section was mentioned the most important Milestones and assets adopted by Ibn Hazm in rooting the rules of jurisprudence, and then the second section we mentioned some applications on some rules of jurisprudence, and in conclusion we presented the most important findings and made some recommendations.